2004
DOI: 10.1111/j.1365-2648.2004.03132.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality monitoring of nurse telephone triage: pilot study

Abstract: External assessment of triage quality may be of only moderate accuracy and reliability. Nonetheless, considerable information can be gleaned from assessing audiotapes to assess consultation quality. Even where nurses are generally highly skilled and competent, a 1% review of triage consultations would be sufficient to identify their information-gathering learning needs in relation to patients' presenting problems. Audio-taped consultations could be an important part of clinical governance strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 22 publications
(27 reference statements)
0
27
0
2
Order By: Relevance
“…However, our trial was not powered to inferentially test safety outcomes and we cannot conclusively rule out diff erences between study groups. In view of this factor and of other evidence, 24,25 caution is needed before fi rm conclusions can be drawn from these results, and further studies, possibly including diff erent study methods such as signifi cant event audit, might provide useful additional evidence about the safety of triage.…”
Section: Discussionmentioning
confidence: 99%
“…However, our trial was not powered to inferentially test safety outcomes and we cannot conclusively rule out diff erences between study groups. In view of this factor and of other evidence, 24,25 caution is needed before fi rm conclusions can be drawn from these results, and further studies, possibly including diff erent study methods such as signifi cant event audit, might provide useful additional evidence about the safety of triage.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 A UK equivalence trial (in which death within 7 days of contact was the primary outcome) established the safety of out-of-hours primary care NT by experienced nurses using computerised decision support software (CDSS) in comparison with usual care (UC). 5 This is supported by work in the UK by the Richards et al 20 study, in which audio tapes of nurse triage consultations to assess decision-making revealed that decision-making was rated by GP or nurse practitioner review to be mostly good, with minimal risk from poor nurse triage decisions. However, one Swedish study 19,21 noted that nurses often used self-care advice and also over-rode software-determined recommendations on management.…”
Section: Patient Safetymentioning
confidence: 91%
“…Richards et al 20 conducted research to assess the quality of information-gathering and accuracy of decision-making by nurses undertaking telephone triage. 20 Independent GP and nurse assessors rated audio-recordings of nurse telephone triage consultations. Out of 218 consultations only 7 (around 3%) were rated as potentially unsafe, suggesting that, overall, nurse telephone triage is safe.…”
Section: Safetymentioning
confidence: 99%
“…72 57 also reported on appropriateness and 11 of the studies identified here were included in the review by Blank et al 73,[75][76][77][80][81][82]84,88,90 This review identified that triage decisions rated as appropriate varied between 44% and 98%. However, many different definitions of appropriateness were used, which leads to difficulty when trying to compare results.…”
Section: Service Impactsmentioning
confidence: 99%